2018
DOI: 10.1002/chem.201800979
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Space In Situ Bond Energies: Toward A Consistent Energetic Definition of Bond Strength

Abstract: A rigorous definition of intrinsic bond strength based on the partitioning of a molecule into real-space fragments is presented. Using the domains provided by the quantum theory of atoms-in-molecules (QTAIM) together with the interacting quantum atoms (IQA) energetic decomposition, we show how an in situ bond strength, matching all the requirements of an intrinsic bond energy, can be defined between each pair of fragments. Total atomization or fragmentation energies are shown to be equal to the sum of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…We have recently shown that total interaction energies E AB int behave as intrinsic bond energies, 21 and can be used to solve several longstanding problems in the appropriate definition of these important quantities. E int 's fullfil all the requisites to be used as rigorous energetic descriptors of bond strength.…”
Section: Bond-energy-bond-order Relation In the Qct/iqa Methodologymentioning
confidence: 99%
“…We have recently shown that total interaction energies E AB int behave as intrinsic bond energies, 21 and can be used to solve several longstanding problems in the appropriate definition of these important quantities. E int 's fullfil all the requisites to be used as rigorous energetic descriptors of bond strength.…”
Section: Bond-energy-bond-order Relation In the Qct/iqa Methodologymentioning
confidence: 99%
“…This is nothing but the textbook Born–Haber cycle, which can be restated in terms of atomic self‐energies. Promoting the free Li and F atoms into their in‐the‐molecule states in diatomic LiF costs 132.1 and −55.7 kcal mol −1 , respectively . These add to a 76.4 kcal mol −1 global penalty that is more than compensated for by the mutual −170.3 kcal mol −1 electrostatic attraction between the formed ions.…”
Section: Introductionmentioning
confidence: 75%
“…The electrostatic contribution is destabilizing, which it must be if two neutral nonoverlapping charge distributions interact . In contrast, a CCSD calculation for LiF provides an opposite energetic partition of EintLiF =−208.1 kcal mol −1 , with EcovLiF =−28.8 and EelsLiF =−179.3 kcal mol −1 . Interestingly, assuming point net QTAIM charges for LiF provides a very good approximation to EelsLiF : Q A Q B / R AB =−184.5 kcal mol −1 (this is only the case in very ionic compounds).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations